Premature onset of cardiovascular disease in HIV-infected individuals: the drugs and the virus. Issue 6 (November 2010) - Maisa, Anna; Westhorpe, Clare; Elliott, Julian; Jaworowski, Anthony; Hearps, Anna C; Dart, Anthony M; Hoy, Jennifer; Crowe, Suzanne M
Life expectancy in HIV-infected individuals has been greatly enhanced through immunologic restoration and virologic suppression resulting from antiretroviral therapy. Current clinical HIV care in Western countries focuses on treatment of drug toxicities and prevention of comorbidities. These non-AIDS HIV-related comorbidities, such as cardiovascular disease, occur even in individuals with virologic suppression and manifest at an earlier age than when normally presenting in the general population. While traditional risk factors are present in many HIV-infected individuals who develop cardiovascular disease, the additional roles of HIV-related chronic inflammation and immune activation as well as chronic HIV viremia may be significant. This review provides current evidence for the contributions of the virus, in terms of both chronic viremia and its contribution via chronic low-level inflammation, immune activation, premature immune senescence and dyslipidemia, to the pathogenesis of HIV-related cardiovascular disease, and balances this against the propensity of specific antiretroviral therapies to cause cardiovascular disease, in particular through altered cholesterol metabolism.